Predictors of Friendship Skills for Adolescents with Asthma: An Analysis of Parent Report on the 2022 National Survey of Children’s Health - Brandon Workman; Laura A. Nabors; Danielle Pierre Hixon; Ashley L. Merianos; Cathleen Odar Stough; Joshua S. Bernstein; Jonathan A. Bernstein (Children, 2025)
Background/Objectives: This study assesses parent reports of adolescent- and parent-level factors related to friendships among adolescents with asthma. This study serves to inform physicians and other health care professionals of factors related to difficulties making friends for adolescents with asthma, providing information from parent reports to identify risk and resilience factors related to friendships. Methods: Adolescents aged 12–17 years with current asthma from the 2022 National Survey of Children’s Health (NSCH) were selected for the study (n = 1812). A weighted logistic regression analysis was performed to explore predictors related to making and keeping friends. Adolescent-level predictors were asthma severity, allergies, body mass index, having behavioral problems, and adolescent sex and race/ethnicity (non-Hispanic White, and others, including Hispanic). Parent-level predictors were parent stress and coping. Results: Adolescents who were female, non-Hispanic White, had moderate/severe asthma symptoms, had current allergies, were overweight, and had behavioral problems were more likely to have difficulty making and keeping friends than adolescents who were male, non-White, had mild asthma, did not have allergies, were a normal weight or underweight, and did not have behavioral problems. Parents who reported difficulty coping with parenthood and its associated stressors were more likely to report that their adolescents had difficulty making friends. Conclusions: Pediatric moderate-to-severe asthma patients whose parents had difficulty coping with stress were more likely to exhibit greater difficulty making and keeping friends. Health care professionals managing these patients should incorporate questions into their history that address behavioral problems and parental household stress growing up to determine optimal strategies for improving friendship relationships. Whether this strategy leads to better asthma control and outcomes requires further investigation. In future studies, case studies with information about changes in friendships over time for adolescents with asthma should be carried out. The case studies could potentially highlight social strategies to use to improve friendship skills, and ultimately friendship-making for this vulnerable group.